2013
DOI: 10.1124/jpet.113.203554
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Pharmacological Characterization of TD-4208, a Novel Lung-Selective Inhaled Muscarinic Antagonist with Sustained Bronchoprotective Effect in Experimental Animal Models

Abstract: Tiotropium is currently the only once-daily, long-acting muscarinic antagonist (LAMA) approved in the United States and other countries for the treatment of chronic obstructive pulmonary disease (COPD). Glycopyrronium has shown promise as a LAMA and was recently approved for once-daily maintenance treatment of COPD in the European Union. Here, we describe the in vivo preclinical efficacy and lung selectivity of a novel inhaled muscarinic antagonist, TD-4208 (biphenyl-2-ylcarbamic acid 1-(2-{[4-(4-carbamoylpipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…In vitro, revefenacin antagonized muscarinic acetylcholine cholinergic receptor-mediated contractions for up to 24 h in rat and guinea pig tracheal tissues, as well as in human airway muscle tissues [ 9 ]. In anesthetized dogs and rats, single or repeated dosing (once daily for 7 days) of inhaled revefenacin provided a dose-dependent bronchoprotection against acetylcholine- or methacholine-induced bronchoconstriction [ 10 ]. The bronchoprotective effect was seen as early as 5 min post-dose and was sustained for up to 24 h. In these animal models, repeated once daily dosing of revefenacin also exhibited superior functional lung selectivity index over repeated dosing of tiotropium (i.e.…”
Section: Scientific Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, revefenacin antagonized muscarinic acetylcholine cholinergic receptor-mediated contractions for up to 24 h in rat and guinea pig tracheal tissues, as well as in human airway muscle tissues [ 9 ]. In anesthetized dogs and rats, single or repeated dosing (once daily for 7 days) of inhaled revefenacin provided a dose-dependent bronchoprotection against acetylcholine- or methacholine-induced bronchoconstriction [ 10 ]. The bronchoprotective effect was seen as early as 5 min post-dose and was sustained for up to 24 h. In these animal models, repeated once daily dosing of revefenacin also exhibited superior functional lung selectivity index over repeated dosing of tiotropium (i.e.…”
Section: Scientific Summarymentioning
confidence: 99%
“…twice daily LAMA therapy). After repeated dosing, the bronchoprotective potency of revefenacin and tiotropium was maintained, unlike glycopyrronium [ 10 ].…”
Section: Scientific Summarymentioning
confidence: 99%
“…In a previous study, we demonstrated that inhaled revefenacin produced potent protection against ACh or MCh evoked bronchoconstriction in dogs and rats . In this study, we investigated the antagonist potency and offset time in isolated tracheal tissues from rat in order to gain mechanistic insight into the long‐acting bronchoprotective effects observed in rats in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Revefenacin (TD‐4208; biphenyl‐2‐ylcarbamic acid 1‐(2‐{[4‐(4‐carbamoylpiperidin‐1‐ylmethyl)benzoyl]methylamino}ethyl)piperidin‐4‐yl ester) (Figure ) is an investigational LAMA, in late‐stage development as a nebulized inhalation solution, that was designed to produce long‐acting bronchodilation, consistent with once‐daily dosing, and with a high degree of lung‐selectivity to avoid systemic antimuscarinic adverse effects such as dry mouth, urinary retention, and constipation . Following inhalation dosing to rats and dogs, revefenacin produced potent protection against the bronchoconstrictor response to ACh or methacholine (MCh) . In both species, the bronchoprotective effect was long‐acting (≥24 hours) and comparable in duration to tiotropium.…”
Section: Introductionmentioning
confidence: 99%
“…1 Revefenacin (YUPELRI R ) inhalation solution, delivered via standard jet nebulization, is an anticholinergic indicated for the maintenance treatment of patients with chronic obstructive pulmonary disease (COPD). [2][3][4] After inhaled administration, revefenacin is rapidly absorbed, with peak concentrations observed within 14 to 31 minutes after the start of nebulization. Absolute bioavailability after oral administration is low (<3%).…”
mentioning
confidence: 99%